A Bahá'í concept of peace as a resource for peace education: Case study of 'The Problem of Prejudice'. Issue 2 (4th May 2022) - Betts Razavi, Tiffani; Mahmoudi, Hoda
ABSTRACT: This article describes a Bahá'í concept of peace in the context of discussions about the nature and focus of peace education, in particular the role of moral education as an element of peace education. It introduces the notions of human nobility and the oneness of humanity as the moral basis for holistic peace within a framework of the collective social evolution of humanity, and explores the idea of identifying, understanding, and removing barriers to unity, specifically in the form of inequalities and prejudices, as the foundation of an approach to peace education. The application of such an approach to a university level course is shared through a case study of 'The Problem of Prejudice', offered by the Bahá'í Chair for World Peace at the University of Maryland, College Park. Key strands of content and pedagogy are described, and qualitative data from students participating in the course in 2021 (n = 20), collected in the form of self-perceptions of changes in knowledge, skills, attitudes and commitment, are presented. The article concludes with a discussion of the learning gained from this study and how a Bahá'í concept of peace may serve as a resource for university peace educators and students.